Shoulder instability in the overhead athlete - DeFroda, S. F.; Goyal, D.; Patel, N.; Gupta, N.; Mulcahey, M. K. (Current Sports Medicine Reports, 2018)
Shoulder instability encompasses a spectrum of disease ranging from subluxation to dislocation, and is typically associated with collision athletes such as wrestlers and football players. Instability, however, also can be the result of repetitive microtrauma, as seen in overhead athletes (baseball, tennis, volleyball, swimming). The presentation of instability can be subtle, and difficult to diagnose in the absence of an acute traumatic event without the proper suspicion, physical examination, and diagnostic evaluation. Overhead athletes present the unique challenge of requiring the glenohumeral joint to exceed its physiologic limits during competition; therefore, injury in this population can be devastating. Additionally, athletes who experience instability, regardless of treatment, require rehabilitation (including periscapular strengthening) to maximize strength of the surrounding musculature. Specifically they will require coordinated throwing programs, and gradual return to play protocols dependent on their sport. This article reviews the specific physiology, diagnosis, and treatment of shoulder instability in this population.